Policemen's perception of their experience working in a high-risk area - Leigh Robinson; Antoinette Gmeiner (AOSIS, 1998)
In this article the results of research, undertaken to explore and describe how single male policemen belonging to one of three identified units experience working in a specific high-risk metropolitan area in Gauteng, are discussed. Opsomming In hierdie artikel word die resultate bespreek om die ervaring van alleenlopende manlike polisiebeamptes, wat aan een van die drie ge'identifiseerde eenhede van 'n spesifieke hoe-risiko metropolitaanse area in Gauteng behoort, te verken en te beskryf. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.